Not All Robotic-assisted Total Knee Arthroplasty Are the Same. Issue 2 (15th January 2021) - Siddiqi, Ahmed; Mont, Michael A.; Krebs, Viktor E.; Piuzzi, Nicolas S.
Abstract : Because value in healthcare has shifted to a measurement of quality relative to the cost, a greater emphasis exists on improving clinical and functional outcomes and patient satisfaction. Despite advances in implant design, surgical technique, and postoperative rehabilitation, multiple studies demonstrate that nearly 20% of patients remain dissatisfied with their overall outcomes after primary total knee arthroplasty (TKA). Because implant positioning, alignment, and equal soft-tissue balance are critical for a successful TKA, malalignment in the coronal, sagittal, and rotational planes continue to increase failure rates and cause poor clinical outcomes. Robotic-assisted TKA has gained momentum within the past 10 years to better control surgical variables by mitigating technical errors caused by insecure cutting guides and imprecise bone cuts. Contemporary robotic platforms have evolved along with our ability to collect high-quality patient-reported outcome measures data, and this combination is proving the clinical effectiveness. This comprehensive review investigates the advent of robotic-assisted TKA including advantages, disadvantages, historical, and commercially available newer generation systems, clinical outcomes, and cost analysis to better understand the potential added value of this technology.